Evaluation of the Efficacy and Safety of Switching to Pasireotide in Patients With Acromegaly Inadequately Controlled With First-Generation Somatostatin Analogs - Gadelha, Mônica; Bex, Marie; Colao, Annamaria; Pedroza García, Elier Mitsael; Poiana, Catalina; Jimenez-Sanchez, Marisela; Yener, Serkan; Mukherjee, Rishav; Bartalotta, Amy; Maamari, Ricardo; Raverot, Gérald (Frontiers in Endocrinology, 2020)
Introduction: Acromegaly is a rare, serious endocrine disorder characterized by excess growth hormone (GH) secretion by a pituitary adenoma and overproduction of insulin-like growth factor I (IGF-I). Transsphenoidal surgery is the treatment of choice, although many patients require additional interventions. First-generation somatostatin analogues (SSAs) are the current standard of medical therapy; however, not all patients achieve control of GH and IGF-I. Outcomes from a Phase IIIb open-label study of patients with uncontrolled acromegaly on first-generation SSAs switching to pasireotide (clinicaltrials.gov: NCT02354508) are reported. Methods: Adults with uncontrolled acromegaly (mean GH [mGH] ≥1µg/L from a five-point profile over 2 hours, and IGFI >1.3x upper limit of normal [ULN]) despite ≥3 months’ treatment with maximal approved doses of long-acting octreotide/lanreotide received open-label long-acting pasireotide 40mg/28 days. Pasireotide dose could be increased (maximum: 60mg/28 days) after week 12 if biochemical control was not achieved, or decreased (minimum: 10mg/28 days) for tolerability. Patients who completed 36 weeks’ treatment could continue receiving pasireotide during an extension (weeks 36–72) when concomitant medication for acromegaly was permitted. Primary endpoint was proportion of patients with mGH <1μg/L and IGF-I <ULN at week 36. Biochemical control was also assessed during the extension. Safety was assessed throughout. Results: 123 patients were enrolled and received pasireotide; 88 patients continued into the extension. Overall, 18 (14.6% [95%CI: 8.9–22.1]) patients achieved mGH <1µg/L and IGFI <ULN at week 36; biochemical control was achieved in 42.9% with screening mGH 1.0–2.5μg/L and 6.4% with screening mGH >2.5μg/L. For patients who entered the extension, 14.8% (95%CI: 8.1–23.9), 12.5% (95%CI: 6.4–21.3), 14.8% (95%CI: 8.1–23.9) and 11.4% (95%CI: 5.6–19.9) had mGH <1µg/L and IGFI <ULN at weeks 36, 48, 60 and 72, respectively. During the overall study period, most frequent investigator-reported drug-related adverse events were hyperglycemia (41.5%), diabetes mellitus (23.6%) and diarrhea (11.4%). Conclusions: Switching to long-acting pasireotide provided biochemical control in some patients, which was sustained with continued treatment. Long-term safety and tolerability of long-acting pasireotide was consistent with the known safety profile. These data support long-acting pasireotide for some patients with acromegaly who are uncontrolled on first generation SSAs.